Rapid ice melting drives Earth's pole to the east. Issue 11 (7th June 2013) - Chen, J. L.; Wilson, C. R.; Ries, J. C.; Tapley, B. D.
Abstract : [1] Space geodetic observations of polar motion show that around 2005, the average annual pole position began drifting toward the east, an abrupt departure from the drift direction seen over the past century. Satellite gravity measurements from the Gravity Recovery and Climate Experiment (GRACE) show that about 90% of this change is due to accelerated melting of polar ice sheets and mountain glaciers and related sea level rise. The close relationship between long‐term polar motion and climate‐related mass redistribution established using GRACE data indicates that accurately measured polar motion data offer an additional tool for monitoring global‐scale ice melting and sea level rise and should be useful in bridging the anticipated gap between GRACE and follow‐on satellite gravity missions. Key Points: First explained the abrupt departure of the mean pole position in recent years. Polar motion provides constraints to study of ice melting and sea level rise. Polar motion is useful in bridging the gap between GRACE and follow‐on missions.